State Failure - Taylor, A. author. aut Link
VII, 259 p.
Keywords: Andrew Taylor provides an overview of the origins, evolution, and impact of state failure since the 1990s. Avoiding quickly outdated country-based case studies, he focuses on failure as a process rather than an event, putting contemporary usage in a wider historical context.